A Christian critique of the state - Philip Vander Elst (Institute of Economic Affairs (IEA), 2008)
Ever since that period in European history known as the '18th century Enlightenment,' the idea has firmly taken root in Western culture that the power of the State should be harnessed and mobilised for beneficial purposes. Whether the objective has been the elimination of poverty or the education of the people, the furtherance of social harmony or the achievement of greater equality of opportunity, there has long been a general tendency amongst most people - including Christians - to view Government as a positive force for good and the best vehicle for achieving positive social change. Confronted by some problem or injustice, most people today typically look to the State for a solution and blame politicians when things go wrong. The purpose of this paper is to challenge this mentality by inviting readers to look more closely at the coercive nature of the State and its negative record in history. By doing so, they will see that overmighty Government and the abuse of State power has been the common factor in war, slavery, political oppression, and religious and ideological persecution. It has also been the chief cause of mass poverty, famine and economic dislocation in the 20th century. Whilst recognising that the State is a necessary institution with legitimate functions, the central argument of this paper is that the moral and material progress of human societies has been directly related to their success in curbing the power of Government and releasing the creative and altruistic energies of individuals and local communities. As a Christian, I also argue that 'loving one's neighbour' and 'doing good,' is primarily a personal responsibility best discharged through the voluntary co-operation of free individuals acting together outside the State. Conversely, excessive reliance on the power of Government stunts the moral growth of individuals and leaves too many decisions in the hands of a coercive institution whose proper functioning is inevitably hindered by the imperfect human nature of the people running it. For these reasons, containing the power of the State is a constant battle that must be fought and won in every generation. This is especially important in the 21st century, when there is so much pressure to increase the remit of Government across national boundaries, whether by centralising power in emerging regional superstates like the European Union, or by moving towards some loose system of world government via the United Nations. Against these pressures and tendencies this paper will, I hope, sound a salutary warning.
Keywords: 330